Efektivitas Video Pembelajaran Berbasis Zenius.Net Dalam Meningkatkan Pemahaman Konsep Kimia Siswa - Baiq Rina Amalia Safitri; Pahriah Pahriah; Muhammad Fuaddunnazmi (Universitas Pendidikan Mandalika Mataram, 2022)
This research has a core objective, namely to find out the effectiveness of the application of Zenius-based learning videos in improving students' understanding of chemical concepts. This research is included in the category of experimental type quantitative research. Meanwhile, the research method chosen was One Group Pretest-Posttest Design, which means that only one research group was used. A total of 17 students were selected from class X and XI MA Anshor Beber as the research population using saturated sampling technique or population research. The data analysis technique used in this study combines descriptive data analysis for the measurement of the mean and inferential statistics for testing the significance of the t-test value. The significance of the Ngain value was tested using a t-test (paired samples t-test) and the results were used to interpret the extent of students' understanding of chemical concepts. The average N-gain of students' conceptual understanding after the application of Zenius-based learning videos is 0.7 with a medium category. The average understanding of students' concepts after treatment (77) was proven to be significantly greater than before being given treatment (34) based on the value of t count = 28.8 which was greater than tcritical = 2.1 for dk = 15 with a p significance value of 0.000. Therefore, it can be concluded that zenius.net-based learning videos are effective in increasing students' understanding of concepts.